Preemptive Analgesia with Acupuncture Monitored by c-Fos Expression in Rats - Gonçalves de Freitas, André T.A. [UNESP]; Lemonica, Lino [UNESP]; De Faveri, Julio [UNESP]; Pereira, Sergio [UNESP]; Bedoya Henao, Maria D. [UNESP] (Medical Association of Pharmacopuncture Institute, 2016)
Pain behavior and awareness are characterized by heightened alertness and anxiety, which begin to disappear as soon as the curative process starts. The present study aimed to quantify c-fos expression in rat spinal cords and brains after a surgical stimulus and with preoperative or postoperative acupuncture. Animals were randomly divided into preoperative and postoperative groups and were then further divided into control, manual acupuncture (MA), or electroacupuncture (EA) groups. Expression of c-fos was quantified using immunohistochemistry. The collected data were analyzed using the t test at a 5% probability level. Presurgery and postsurgery spinal cord c-fos expressions were similar in all of the treatment groups. In the control rats, c-fos expression was higher before surgery than after surgery, contradicting the expected outcome of acupuncture and preemptive analgesia. After treatment, the expression of c-fos in the brains of the rats in the MA and the EA groups was reduced compared with that of the rats in the control group. These findings suggest that acupuncture used as preemptive analgesia in rats is a useful model for studying its application in human treatment.
Keywords: Acupuncture; Analgesia; C-fos protein; Pain